Malakoplakia associated with diarrhoea and colonic lesions after rituximab treatment - Yaqoub Alshatti; Meshaan Alenezi (European Journal of Case Reports in Internal Medicine)
Malakoplakia is a rare granulomatous condition that occurs due to defective lysosomal digestion during phagocytosis and can mimic inflammatory bowel disease (IBD) or malignancies, particularly in immunosuppressed patients. We report the case of a 62-year-old male with IgG4-related orbitopathy, who developed persistent diarrhoea and colonic lesions 6 weeks after receiving rituximab therapy for nephrotic syndrome secondary to membranoproliferative glomerulonephritis. Colonoscopy revealed pancolitis with mucosal granularity, loss of vascular pattern, and small nodules, raising initial suspicion for IBD. However, histological analysis of colonic biopsies confirmed malakoplakia with the presence of Michaelis-Gutmann bodies, pathognomonic for this condition. The patient was treated with ciprofloxacin for 2 weeks, and steroids were discontinued, leading to complete symptom resolution and significant histological improvement. During follow-up, the number and size of white lesions decreased, and no Michaelis-Gutmann bodies were detected. This case underscores the importance of maintaining a broad differential diagnosis for gastrointestinal lesions in immunosuppressed patients, as misdiagnosis can result in inappropriate escalation of immunosuppressive therapy. Recognizing the characteristic histopathology of malakoplakia and linking it with clinical findings are critical for timely diagnosis and effective management. This report adds to the limited literature on rituximab-associated malakoplakia, highlighting the unique challenges in its diagnosis and treatment.